2019
DOI: 10.1021/acs.iecr.9b04774
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Particle Size in a Helical Coil Reactor

Abstract: This study investigates the effect of initial reactant concentration, residence time, and flow on the particle size and particle size distribution produced by single-phase reactive precipitation between BaCl2 and Na2SO4 in a helical coil reactor. Helical coils offer enhanced mixing due to the secondary flow generated by the imbalance of centrifugal forces. The particles produced in a helical coil reactor are found to have smaller sizes and narrower size distribution compared to a straight tube reactor under si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…These devices have been used as plug-flow crystallizers in continuous antisolvent crystallization. For example, Pal et al implemented reactive precipitation between BaCl 2 and Na 2 SO 4 using helical coils, and it was found that smaller particles can be produced using helical coils compared with straight tubes . Benitez-Chapa et al used CFIs to carry out continuous antisolvent crystallization of flufenamic acid, and it was found that the crystal mean size of the final product decreased as the number of 90° flow inverters increased .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These devices have been used as plug-flow crystallizers in continuous antisolvent crystallization. For example, Pal et al implemented reactive precipitation between BaCl 2 and Na 2 SO 4 using helical coils, and it was found that smaller particles can be produced using helical coils compared with straight tubes . Benitez-Chapa et al used CFIs to carry out continuous antisolvent crystallization of flufenamic acid, and it was found that the crystal mean size of the final product decreased as the number of 90° flow inverters increased .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pal et al implemented reactive precipitation between BaCl 2 and Na 2 SO 4 using helical coils, and it was found that smaller particles can be produced using helical coils compared with straight tubes. 15 Benitez-Chapa et al used CFIs to carry out continuous antisolvent crystallization of flufenamic acid, and it was found that the crystal mean size of the final product decreased as the number of 90°flow inverters increased. 16 Orehek et al (2022) utilized CFIs to implement multi-segment multi-addition continuous antisolvent crystallization of benzoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Different static mixing elements and configurations have been used to achieve fluid mixing depending on process requirements and pressure drop. Enhanced mixing in static mixers leads to improved heat transfer. ,, Furthermore, in crystallization studies, supersaturation gradients can be minimized with static mixers, which results in products with a narrower particle size distribution compared to devices without flow switching. The ideal static mixer is one in which efficient mixing can be achieved with a low pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating transport phenomena in helically coiled tubes is still of great interest [7,8,[21][22][23]. Especially non-invasive imaging approaches promise great insights and are crucial for the validation of numerical simulations [24].…”
Section: Introductionmentioning
confidence: 99%